تطوّر الاستيطان في مدينة القدس - باهي, فاتح (جامعة الوادي - University of Eloued, 2018)
Settlement is the cornerstone of the thought of the Zionist movement, and the first basis for imposing the new occupation status quo on the city of Jerusalem, and the Zionist settlement differs from other types of colonial settlement that the world has known in the modern and contemporary era, as it relies on its grounds and justifications on religious pretexts and allegations, and during the stages of the Zionist conflict. The Islamic settlement constituted the means and the goal at the same time, as it was not limited to being a physical building process only, but rather went beyond that, as it is a means of demolishing and undermining the Arab Islamic society in itself.
مقال
Keywords: الاستيطان، الحركة الصهيونية، فلسطين، القدس